The Implementation of Video as Instructional Media in Oral Presentation Class - Hamidah, Yeyen (2016)
The use of certain media plays an important role to attract students' motivation to participate in the classroom. The use of video as instructional media is considered to be able to attract students' motivation. The integrated activities on using video can assist a lecturer in realizing students' participation. This research aims at investigating how the video is used as instructional media in oral presentation class, students' responses to the implementation, and its effectiveness to students' presentation skills. This is a mixed-method study with three research instruments: observation, questionnaire and score analysis. The data of the observation was analyzed qualitatively to elaborate how the video was used as instructional media in oral presentation class. While the data of the questionnaire was analyzed quantitatively to describe students' responses to the implementation of video as instructional media. Finally, the score analysis was analyzed quantitatively to present the effect of using video as instructional media in oral presentation class based on pretest and post-test score. The result of the observation showed that the integrated activities were conducted to make the teaching and learning process successful. The integrated activities were responded positively by the students as shown from the result of the questionnaire; 23 students (63.89%) agreed that the teaching and learning process can motivate them to fully participate in the classroom. The Independent t-test was conducted to compare the oral presentation score of experimental group and control group. There was a significant difference in the score for experimental group (average= 82,67) and control group (average= 70,92) conditions; sig. Value= 0.000 (<0.05). These results suggests that the use of video as instructional media gives a significant effect to students' oral presentation skills.,---Penggunaan media tertentu memiliki peranan penting untuk menarik motivasi siswa untuk berpartisipasi di dalam kelas. Penggunaan video sebagai media instruksional dianggap mampu untuk menarik motivasi siswa. Integrated Activities dalam penggunaan video mampu membantu seorang pengajar untuk membuat siswa berpartisipasi. Penelitian ini bertujuan untuk menginvestigasi bagaimana video digunakan sebagai media instruksional di kelas presentasi, respons siswa terhadap implementasinya, dan efektifitas penggunaan video terhadap kemampuan presentasi siswa. Penelitian ini adalah sebuah penelitian Mixed Methode dengan menggunakan tiga instrumen penelitian yaitu observasi, kuesioner, dan analisa skor. Data dari observasi dianalisa dengan metode kualitatif untuk menggambarkan bagaimana video digunakan sebagai media instruksional dalam kelas presentasi Bahasa Inggris. Sedangkan data dari kuesioner dianalisa dengan menggunakan metode kuantitatif untuk mengetahui respons siswa terhadap pelaksanaan penggunaan video sebagai media instruksional. Serta data dari analisa skor dianalisa dengan menggunakan metode kuantitatif untuk menampilkan efek dari penggunaan video sebagai media instruksional berdasarkan skor pre-test dan post-test. Hasil dari observasi menunjukkan bahwa Integrated Activities telah dilaksanakan untuk mensukseskan proses belajar dan mengajar. Integrated Activities mendapatkan respon positif dari siswa sebagaimana yang bisa dilihat dari hasil kuesioner bahwa 23 siswa (63.89%) setuju bahwa Integrated Actitivies bisa memotivasi mereka untuk berpartisipasi penuh di dalam kelas. Untuk membandingkan nilai presentasi siswa pada kelas eksperimental dan kelas kontrol, maka Independent T-test digunakan untuk menganalisa hal tersebut. Dari hasil uji statistik, dapat diketahui bahwa terdapat perbedaan yang siginifikan antara kelas eksperimental dan kelas kontrol. Rata-rata nilai presentasi kelas eksperimental adalah 82.67 sedangkan rata-rata kelas kontrol adalah 70.92 dengan nilai signifikansi 0.000 (<0.05). Hal ini menunjukkan bahwa penggunaan video sebagai media instruksional memberikan efek yang signifikan terhadap kemampuan presentasi lisan siswa.